Posttranslational modifications in pathogenesis of PCOS - Wei, Huimei; Huo, Peng; Liu, Shun; Huang, Hua; Zhang, Shun (Frontiers in Endocrinology, 2022)
PCOS is the most common endocrine disorder estimated to affect 8–13% of women of reproductive age worldwide. PTMs play an important role in changes in protein function and are necessary to maintain cellular viability and biological processes, thus their maladjustment can lead to disease. More and more studies have reported the association between PCOS and posttranslational modifications. This review summarizes how common and novel PTMs influence the development of PCOS. It provides not only ideas for future research on the mechanism of PCOS but also ideas for PCOS treatments with therapeutic potential.